Morphology and sediment structures in Golfo Dulce, Costa Rica - Hebbeln, Dierk (1996)
Sediment echosounder records (18 KHz) of 14 profiles were made in the fjord-like embayment of Golfo Dulce. Pacific of Costa Rica. to investigate morphology and sediment structure. The NW-SW section includes an oriental fault that is the main internal tectonic characteristic of the Gulf; that has a very steep slope and reaches 170 m in height. Two parallel. but less prominent tectonic faults are also evident on the echographs. The sediments in the flat inner basin consist mainly of turbidites, which reach the deepest part of Golfo Dulce by channels. leaving most of the slope sediments unaffected.